A protocol for a cluster-randomized controlled trial testing an empowerment intervention to prevent sexual assault in upper primary school adolescents in the informal settlements of Nairobi, Kenya - Clea Sarnquist; Jennifer Lee Kang; Mary Amuyunzu-Nyamongo; Gabriel Oguda; Dorothy Otieno; Benjamin Mboya; Nancy Omondi; Duncan Kipkirui; Michael Baiocchi (BMC, 2019)
Abstract Background Sexual violence against adolescents is prevalent worldwide and results in significant physical and mental injuries as well as loss of economic and personal potential. Urban informal settlements such as those around Nairobi, Kenya have been shown to have especially high incidences of violence. Research has shown that empowerment interventions for female adolescents can reduce sexual assault. However, these interventions have had limited testing in urban informal settlements, with young adolescents, or in coordination with complementary programs for male adolescents. Methods/design This study was a two-arm, parallel, cluster-randomized trial testing a combination of a previously-tested girls' intervention, IMPower, and a newly revised boys' intervention, Source of Strength. Clusters were defined as schools within the informal settlements; participants were adolescent girls and boys in class 6, generally between the ages of 10-14 at baseline. Data collection began in January 2016 and continued through December 2018. The primary outcome was the change in incidence of self-reported sexual assault among girls from baseline, compared to a life skills standard of care intervention. Secondary outcomes included experiences of physical and emotional violence, as well as determining the effects of the intervention on self-efficacy, self-esteem, and gender attitudes and beliefs, and how those effects led to changes in experience of sexual assault. For the primary outcome and several of the secondary outcomes, we used an intention to treat estimand. Discussion This was the first randomized controlled trial with longitudinal follow-up of an empowerment self-defense approach to violence prevention for adolescents in informal settlements. The large size and rigorous design supported analysis to understand multiple subgroup experiences in the hypothesized reduction in sexual assault. The study was also unique in its focus on young (10-14 years of age) adolescents and in engaging both boys and girls in separate but coordinated curriculums. The focus on a highly vulnerable and understudied population will make it a significant contribution to the literature on violence prevention. Trial registration Clinical Trials.gov #NCT02771132. Version 3.1 registered May 2017, first participant enrolled January 2017. Retrospectively registered.